Ekstrak etanol buah naga merah (Hylocereus polyrhizus) memperbaiki profil lipid tikus (Rattus Norvegicus) wistar jantan dislipidemia sama efektif dengan statin - Sharan Sharan (Intisari Sains Medis, 2017)
Dyslipidemia is one of the risk factor causing atherosclerosis, which is the main cause of cardiovascular disease and later can leads to death. Proper balanced diet and exercise are the main way to lower down lipid level. If the nonpharmacolgy interventions doesn’t give satisfactory result, the use of  medicine such as statin, which is the gold standard for dyslipidemia can be applied. It is also important to find out  the effects of nature herbs such as red dragon fruit on dyslipidemia. Dragon fruit contains anthocyanin, which is one type of flavonoid found in many dragon fruits that can improve dislipidemic. The aim of this thesis is to prove the effect of red dragon fruit in improving serum lipid profile (total cholesterol, triglycerides, LDL cholesterol and HDL cholesterol) in male dyslipidemic rats as effective as Statin.This study was purely experimental  research by using pre-posttest control group design. This study used 24 male white rats (albino rat) with dislipidemia as a sample. For 28 days the entire male rats were given high-cholesterol diet. The male rats were randomly divided into 3 groups, each group consisted  of  eight rats. The First group were given a standard diet and placebo in the form of distilled water. The Second group were given a standard diet and dragon fruit extract  120 mg/ 200g body weight. The Third  group were given a standard diet  and statin 10mg/200g body weight. All the groups were given treatment once a day for 28 days. Result showed that there was significant reduction in lipid level in second and third group, total cholesterol level reduction of each 73,41mg/dl and 94mg/dl (p<0,05), Triglyceride level reduction of 25.38mg/dl and 53.13mg/dl (p<0,05), LDL level reduction of 20.39mg/dl and 47.96mg/dl (p<0.05), and increase in HDL level of 12.36mg/dl and 32.38mg/dl as compared to first group which was treated with distilled water.It can be concluded that dragon fruit extract and statins are equally effective to improved lipid profile level in male dyslipidemic witsar rats , but statin potency is more powerful than red dragon fruit extract in improving the lipid profile.